2019
DOI: 10.1021/acsomega.9b01392
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glycation-Induced Aggregation of Human Serum Albumin by Organic–Inorganic Hybrid Nanocomposites of Iron Oxide-Functionalized Nanocellulose

Abstract: Protein aggregation leads to the transformation of proteins from their soluble form to the insoluble amyloid fibrils and these aggregates get deposited in the specific body tissues, accounting for various diseases. To prevent such an aggregation, organic–inorganic hybrid nanocomposites of iron oxide nanoparticle (NP, ∼6.5–7.0 nm)-conjugated cellulose nanocrystals (CNCs) isolated from Syzygium cumini (SC) and Pinus roxburghii (PR) were chemically synthesized. Transmission electron microscopy (TEM) images of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…It should be mentioned here that DH− CNO and LC−CNO also showed inhibition toward HEWL and Aβ42 aggregation, which is in contrast to our previous report where plant-based CNCs were found to initially enhance the aggregation process. 52 Thus, it can be suggested that changing the morphology from CNC to CNO provided the appropriate curvature for interaction which possibly helped in the inhibition of protein aggregates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It should be mentioned here that DH− CNO and LC−CNO also showed inhibition toward HEWL and Aβ42 aggregation, which is in contrast to our previous report where plant-based CNCs were found to initially enhance the aggregation process. 52 Thus, it can be suggested that changing the morphology from CNC to CNO provided the appropriate curvature for interaction which possibly helped in the inhibition of protein aggregates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…
Fig. 6 (a) Reaction of CDAP treatment on BNC for protein conjugation [ 80 , 189 ]; (b) Comparison of BSA uptake (left) and release (right) profiles through conventional loading and high-speed loading technique [ 186 ]; (c) in vitro protein release profile from nanocellulose hydrogels within first 48 h [ 190 ]; (d) Schematic presentation of inhibition of glycation-induced aggregation of HSA by Iron Oxide-Functionalized nanocellulose [ 191 ].
…”
Section: Delivery Of Active Molecules/therapeutic Agentsmentioning
confidence: 99%
“…In another study, Singla et al. fabricated an organic-inorganic nanocomposite of CNCs conjugated with iron oxide nanoparticles to inhibit HSA protein aggregation [ 191 ]. In vitro studies have shown that CNC nanocomposites reduce aggregation-induced cytotoxicity in HEK-293 cells by maintaining Ca 2+ ion channels and scavenging intracellular oxygen molecules ( Fig.…”
Section: Delivery Of Active Molecules/therapeutic Agentsmentioning
confidence: 99%
See 2 more Smart Citations